Exploring the Interplay Between Oral Diseases, Microbiome, and Chronic Diseases Driven by Metabolic Dysfunction in Childhood - Fernanda Maria Sabella; Simone Nataly Busato de Feiria; Apoena de Aguiar Ribeiro; Letícia Helena Theodoro; José Francisco Höfling; Thaís Manzano Parisotto; Cristiane Duque (Frontiers Media S.A., 2021)
Oral childhood diseases, such as caries and gingivitis, have much more than a local impact on the dentition and tooth surrounding tissues, which can affect systemic conditions. While the mouth is frequently exposed to microbial stressors that can contribute to an inflammatory state in the entire body, chronic disorders can also interfere with oral health. Sharing common risk factors, a dynamic interplay can be driven between 1. dental caries, gingivitis, and type I diabetes mellitus, 2. early childhood caries and obesity, and 3. caries and cardiovascular diseases. Considering that there are ~2.2 billion children worldwide and that childhood provides unique opportunities for intervention targeting future health promotion, this review is of prime importance and aimed to explore the relationship between the oral microbiome and oral chronic diseases driven by metabolic dysfunction in childhood.